Calculați:

3x + 2y + (2x + 5y) = ?

x + 7y

5x - 3y

5x + 7y

x - 3y

1

Calculați:

3x + 4y + (2x - 5y) = ?

x + 9y

x - y

5x - y

5x + 9y

1

Calculați:

x + 3y + (-x + 6y) = ?

2x - 3y

2x + 9y

-3y

9y

1

Calculați:

7x + 2y + (-3x - 4y) = ?

10x + 6y

10x - 2y

4x + 6y

4x - 2y

1

Calculați:

x + 4y - (2x + 3y) = ?

-x + 7y

3x + 7y

3x + y

-x + y

1

Calculați:

2x + 3y - (5x - 4y) = ?

7x + 7y

7x - y

-3x + 7y

-3x - y

1

Calculați:

6x + 2y - (-x + 2y) = ?

7x + 4y

7x

5x + 4y

5x

1

Calculați:

x + 4y - (-2x - 4y) = ?

3x + 8y

-x + 8y

-x

3x

1

Calculați:

2x - 5y + (x + 2y) = ?

x - 3y

3x - 7y

3x - 3y

x - 7y

1

Calculați:

3x - y + (x - y) = ?

4x - 2y

2x

4x

2x - 2y

1

Calculați:

5x - 2y + (-3x + 7y) = ?

8x + 5y

2x - 9y

2x + 5y

8x - 9y

1

Calculați:

6x - 4y + (-x - 4y) = ?

7x

5x - 8y

5x

7x - 8y

1

Calculați:

3x - 6y - (2x + y) = ?

5x - 7y

x - 5y

5x - 5y

x - 7y

1

Calculați:

4x - 2y - (3x - 4y) = ?

7x - 6y

x - 6y

x + 2y

7x + 2y

1

Calculați:

x - y - (-2x + 3y) = ?

3x - 2y

-x + 2y

3x - 4y

-x - 4y

1

Calculați:

3x - y - (-5x - 4y) = ?

-2x - 5y

8x + 3y

8x - 5y

-2x + 3y

1

Calculați:

-3x + 4y + (2x + 5y) = ?

x - y

x + 9y

-x + 9y

-x - y

1

Calculați:

-2x + 6y + (7x - y) = ?

5x + 5y

5x + 7y

9x + 5y

9x + 7y

1

Calculați:

-x + 3y + (-2x + 4y) = ?

x - y

-3x + 7y

x + 7y

-3x - y

1

Calculați:

-4x + 2y + (-3x - 4y) = ?

-7x + 6y

-7x - 2y

-x - 2y

-x + 6y

1

Calculați:

-3x + 5y - (2x + 3y) = ?

-x + 8y

-5x + 2y

-x + 2y

-5x + 8y

1

Calculați:

-2x + 3y - (5x - 4y) = ?

3x + 7y

-7x + 7y

-7x - y

3x - y

1

Calculați:

-6x + 2y - (-x + 2y) = ?

-7x

-5x

-7x + 4y

-5x + 4y

1

Calculați:

-x + 4y - (-2x - 4y) = ?

-3x + 8y

x + 8y

-3x

x

1

Calculați:

-2x - 5y + (x + 3y) = ?

-x - 8y

-x - 2y

-3x - 8y

-3x - 2y

1

Calculați:

-3x - 2y + (x - y) = ?

-2x - y

-4x - y

-4x - 3y

-2x - 3y

1

Calculați:

-5x - 3y + (-2x + 7y) = ?

-7x + 4y

-3x + 4y

-7x - 4y

-3x - 4y

1

Calculați:

-6x - 4y + (-2x - 3y) = ?

-4x - 7y

-4x - y

-8x - 7y

-8x - y

1

Calculați:

-3x - 6y - (2x + 4y) = ?

-5x - 10y

-x - 10y

-x - 2y

-5x - 2y

1

Calculați:

-4x - 2y - (3x - 4y) = ?

-7x + 2y

-7x - 6y

-x - 6y

-x + 2y

1

Calculați:

-2x - y - (-3x + 2y) = ?

-5x -3y

x - 3y

-5x + y

x + y

1

Calculați:

-5x - 2y - (-5x - 10y) = ?

-10x + 8y

-12y

-10x - 12y

8y

1

Credem în educația gratuită și în dreptul la educație. Contact: [email protected]
2007-2019 invatasingur.ro